101 key terms in philosophy and their importance for theology - Clark, Kelly James, 1956-; Lints, Richard; Smith, James K. A., 1970- (Louisville, Westminster John Knox Press., 2004)
Written by two philosophers and a theologian, this book provides easy access to key terms in philosophy and how they are understood and used in theology. The focused entries discuss what the terms have meant in classical and contemporary philosophy and then shift to what these philosophical understandings have meant in the history of Christian theology to the present day. The result is a unique volume that clearly shows the interplay of these disciplines and how theology has been influenced by the language and vocabulary of philosophy.--Publisher
Aesthetics -- Analytic/continental philosophy -- Anselm -- Anthropomorphic language -- Apologetics -- Aquinas, Thomas -- Aristotle -- Atheism -- Augustine -- Being and goodness -- Cause/causality -- Common sense philosophy -- Cosmology -- Deconstruction -- Descartes, Rene -- Dualism/monism -- Enlightenment -- Epistemology -- Essence/essentialism -- Eternal/everlasting -- Ethics -- Ethics, biblical -- Euthyphro problem -- Evil, problem of -- Existentialism -- Faith -- Faith and reason -- Feminism/feminist philosophy -- Feuerbach, Ludwig -- Free will -- Freud, Sigmund -- God, belief in -- God, nature of --
Includes bibliographical references (pages 101-111) and index.
Keywords: Christianity -- Philosophy -- Terminology; Dictionaries